Modeling approaches to redesign ruminant production toward sustainability—the state of the art from a literature perspective - Lobo, Annelise Aila Gomes; Campana, Mariana; Gameiro, Augusto Hauber; Morais, Jozivaldo Prudêncio Gomes de (Frontiers in Environmental Science, 2024)
Integrated systems allow the redesign of productive landscapes due to the insertion of different species of trees and shrubs. A diversified pasture provides the animal with a wider range and a greater amount of phytonutrients than animals fed on grains, and beyond that, tree legumes have great potential for producing biomass with excellent levels of crude protein, as well as the capacity for symbiotic nitrogen fixation. Assuming that modeling can be a relevant tool to address systemic changes, we sought to answer the following question: “how can ruminant husbandry systems be modeled to help farmers, considering the combination of pasture and crop production?” Thus, this work aims to create a modeling framework to guide the redesign of productive landscapes for ruminants in tropical conditions at the farm level. The activities to be carried out will be divided into four stages: a) bibliographical research on existing indicators and/or models for ruminant livestock farming; b) writing opinion articles (already published) and review articles (this article); c) indicating parameters for modeling the redesign of ruminant production landscapes with the use of multifunctional forage plants; and d) demonstrating the novelty by building a decision-making model for rural properties. The hypothesis of this work is that the redesign of multifunctional production landscapes can be guided by modeling obtained from experimental variables that already exist and/or are under construction, as well as from published literature.